Elections and the public expenditure mix - Ana Barreira; Rui Nuno Baleiras (European Regional Science Association (ERSA), 2004)
The paper presents an intertemporal utility model that determines the effects of elections on the public expenditure composition. Conventional political budget cycle models describe incumbents as concerned only with the conditions that guarantee re-appointment. Aiming at achieving re-election, incumbents behave opportunistically in order to seduce voters about their political performance. The paper introduces another motivation for the manipulation of the public expenditure mix near elections: the incumbent's concern with her future utility in the case of defeat. We provide data to suggest that both central and local governments in the European Union do manipulate the budget composition around election moments. In order to rationalise this observation, the paper proposes a model where voters and incumbent are rational, have complete information and no bias towards any category of public expenditure, namely consumption expenditure or investment expenditure. The paper shows that even under these extreme conditions, an electorally induced cycle on public expenditure mix is still expected, one where consumption expenditure raises relative to investment expenditure in pre-election periods. This opportunistic budget manipulation follows from two facts. First, any decision an incumbent makes on consumption expenditure pays back political dividends during the same period the expenditure is incurred, while any investment expenditure only becomes visible to voters with a one-period delay. Second, re-election is an uncertain event, which makes the second state of nature valuable. Outside politics, the incumbents' pay back is a direct function of the voters' assessment of the incumbents' job while in office. The model is then extended to accommodate the scenario where voters and society at large do not share preferences. When voters or society evidence a preference prone to one of the public expenditure categories, a bias towards such category emerges in post-election periods. In pre-election periods two cases are found. Consumption expenditures exceed investment expenditures if either voters or society prefer the former category at the margin. The cycle's nature is ambiguous if the marginal preferences of voters or society are biased towards investment expenditures. JEL classification: H50, E62. Keywords: Political Budget Cycles, Public Expenditure, Elections.
Keywords: H50; E62; 330; Political Budget Cycles; Public Expenditure; Elections